Решите уравнение

2 — 4)2 + (х2 — 3х -10)2 = 0

РЕШЕНИЕ

По теореме Виета разложим многочлен из 2-й скобки на множители.

Для этого решим его как квадратное уравнение:

х2 — 3х -10 = 0

D = b2 — 4ac = (-3)2 — 4*1*(-10) = 9 + 40 = 49,> 0 (2 корня)

Задание 20 Вариант 38

(х + 2)2 = 0    или (х — 2)2 +(х — 5)2 = 0

1.  (х + 2)2 = 0 

      х — 2 = 0

      х = — 2

2.  (х — 2)2 +(х — 5)2 = 0

      х2 — 4х +4 + х2 — 10х + 25 = 0

     2х2 — 14х + 29 = 0

D = b2 — 4ac = 142 — 4*2*29 =

=196 — 232 < 0, нет корней.

Ответ: — 2